PENERAPAN ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PEMILIHAN JAJANAN TRADISIONAL DI PASAR TRADISIONAL TABANAN - Thiar Prahitadani, Kadek; Hartiati, Amna; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2014)
There are many traditional snacks that spread out at Tabanan traditional market. This issues caused a difficulties to choose those traditional snacks. This research has a purpose to knowing about traditional snacks grouping and to define the criteria and alternative of chosing the foods. In the process of defining of choise, here used the Analytical Hierarchy Process (AHP), to find the prioriy of criteria and alternative. Data obtained by interviewing fill out quistionaire by five experts on this subject. From data analising, shows that priority criteria to choose the traditional snacks are appearance (0.409), followed by taste (0.188), way to serve (0.183), then price and packaging with priority value each are (0.127) and (0.094). And priority alternative based on category wet are bubur sumsum” with value 1.821, followed by “daluman” 1.238, “kolak”0.964, “bubur campur” 0.475, and “cendol” with value 0.457. Semi wet category are “klepon” 1.500, followed by “bantal” 1.303, “laklak” 0.918, “sumping” 0.866, and then “lukis” 0.412. Category of dry “matahari” 1.952, followed by “begina” 1.045, “uli” 0.884, “satuh” 0.566 and then “sirat” 0.553.
Keywords: 16